The challenges of strengthening islamic librarianship: retrospect history to shape the future / Mohammad Fazli Baharuddin and Shaharom TM Sulaiman. - Baharuddin, Mohammad Fazli; Sulaiman, Shaharom TM (Universiti Teknologi MARA Cawangan Selangor, 2018)
This article briefly browses through the role of Islamic librarianship based on the history of the Islamic scholarship tradition which saw the emergence of the idea of Islamic librarianship as the discussion focus of this article. There are librarianship scenarios in the Muslim world discussed briefly, initiatives that have been taken towards the idea of Islamic librarianship and the challenges to make it a reality.